Nano‐Enabled Reposition of Proton Pump Inhibitors for TLR Inhibition: Toward A New Targeted Nanotherapy for Acute Lung Injury. Issue 3 (23rd November 2021) - Sun, Liya; Liu, Yuan; Liu, Xiali; Wang, Rui; Gong, Jiameng; Saferali, Aabida; Gao, Wei; Ma, Aying; Ma, Huiqiang; Turvey, Stuart E.; Fung, Shan‐Yu; Yang, Hong
Abstract: Toll‐like receptor (TLR) activation in macrophages plays a critical role in the pathogenesis of acute lung injury (ALI). While TLR inhibition is a promising strategy to control the overwhelming inflammation in ALI, there still lacks effective TLR inhibitors for clinical uses to date. A unique class of peptide‐coated gold nanoparticles (GNPs) is previously discovered, which effectively inhibited TLR signaling and protected mice from lipopolysaccharide (LPS)‐induced ALI. To fast translate such a discovery into potential clinical applicable nanotherapeutics, herein an elegant strategy of "nano‐enabled drug repurposing" with "nano‐targeting" is introduced to empower the existing drugs for new uses. Combining transcriptome sequencing with Connectivity Map analysis, it is identified that the proton pump inhibitors (PPIs) share similar mechanisms of action to the discovered GNP‐based TLR inhibitor. It is confirmed that PPIs (including omeprazole) do inhibit endosomal TLR signaling and inflammatory responses in macrophages and human peripheral blood mononuclear cells, and exhibits anti‐inflammatory activity in an LPS‐induced ALI mouse model. The omeprazole is then formulated into a nanoform with liposomes to enhance its macrophage targeting ability and the therapeutic efficacy in vivo. This research provides a new translational strategy of nano‐enabled drug repurposing to translate bioactive nanoparticles into clinically used drugs and targeted nano‐therapeutics for ALI. Abstract : A new concept of "nano‐enabled drug repurposing" is proposed based on understanding the nanoparticle‐immune system interactions to empower the existing drugs for new uses. Herein, the proton pump inhibitors are identified to share similar mechanisms of action to bioactive gold nanoparticles with undiscovered Toll‐like receptor inhibitory and anti‐inflammatory activities, facilitating the translation of bioactive nanoparticles into clinically applicable nanotherapeutics.